Buxoro amirligi mang‘itlar sulolasi davrida Samarqand bekligida hunarmadchilik va savdo munosabatlari rivojlanishi tarixi (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the place of Samarkand in the history of the Bukhara Emirate, as well asits crafts, internal and external trade relations, based on historical sources. As one of the cities thatmade a significant contribution to world civilization, the development of urban crafts during the reignof the Mangid dynasty of the Samarkand Bekliy can be seen from the fact that great attention waspaid to trade issues and paper production in Samarkand. The fact that their historical monuments havebeen preserved for centuries has amazed people even in the memoirs of this period. It is emphasizedthat the tomb of Amir Temur, made of artificial stone, still exists in Samarkand, and that there areeven more historical monuments in this city. We can see that in the 18th century, the Samarkandprincipality of the Bukhara Emirate had a special place in crafts and trade